1996
DOI: 10.1021/jm9600205
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of 1,4-Dihydropyridine and Pyridine Derivatives with Adenosine Receptors:  Selectivity for A3 Receptors

Abstract: 1,4-Dihydropyridine and pyridine derivatives bound to three subtypes of adenosine receptors in the micromolar range. Affinity was determined in radioligand binding assays at rat brain A1 and A2A receptors using [3H]-(R)-PIA [[3H]-(R)-N6-(phenylisopropyl)adenosine] and [3H]CGS 21680 [[3H]-2-[[4-(2-carboxyethyl)phenyl]ethylamino]-5'-(N-ethylcarbamoyl++ +) adenosine], respectively. Affinity was determined at cloned human and rat A3 receptors using [125I]AB-MECA [N6-(4-amino-3-iodobenzyl)-5'-(N-methylcarbamoyl)ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
150
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(151 citation statements)
references
References 40 publications
1
150
0
Order By: Relevance
“…27,28) have been reported as new hA 3 AR antagonists. Although these antagonists showed strong hA 3 AR antagonistic activity and good selectivity against other adenosine receptor subtypes, they were found to be weak or ineffective against rat A 3 AR (rA 3 AR), 1,11,12,15,28,29) and could therefore not be evaluated in rat in vivo models. The homology of A 3 AR among several species was reported and the only 72% homology between human and rat A 3 AR was one reason for species differences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…27,28) have been reported as new hA 3 AR antagonists. Although these antagonists showed strong hA 3 AR antagonistic activity and good selectivity against other adenosine receptor subtypes, they were found to be weak or ineffective against rat A 3 AR (rA 3 AR), 1,11,12,15,28,29) and could therefore not be evaluated in rat in vivo models. The homology of A 3 AR among several species was reported and the only 72% homology between human and rat A 3 AR was one reason for species differences.…”
mentioning
confidence: 99%
“…As human adenosine A 3 receptor (hA 3 AR) antagonists, many potent and selective antagonists, such as xanthine derivatives, 11) 1,4-dihydropyridines, [12][13][14][15] triazoloquinazolines, 16,17) flavonoids, 18) triazolonaphthyridines, 19) thiazolopyrimidines, 19,20) isoquinolines, 21,22) quinazolines, 21) pyrazolotriazolopyrimidines, [23][24][25] thiazoles and thiadiazoles, 26) and triazolopurines 27,28) have been reported as new hA 3 AR antagonists. Although these antagonists showed strong hA 3 AR antagonistic activity and good selectivity against other adenosine receptor subtypes, they were found to be weak or ineffective against rat A 3 AR (rA 3 AR), 1,11,12,15,28,29) and could therefore not be evaluated in rat in vivo models.…”
mentioning
confidence: 99%
“…Moreover, the binding data of theophylline, 1,3-dipropyl-8-cyclopentylxanthine (DPCPX) and some selective adenosine receptors, included as antagonist reference compounds in Table 2, are also reported. [37][38][39][40][41][42][43][44][45][46][47] Examination of the binding results listed in Table 1 indicated that, the data obtained confirmed the structural modifications carried out on the 5-position of the tricyclic system 1 produces a remarkable modification of the adenosine receptorial profile in terms of affinity and/or selectivity.…”
Section: Resultsmentioning
confidence: 70%
“…Also, the effect of the stereochemistry at the C 4 center has been evaluated, demonstrating that the S-isomer shows better affinity (about 35-fold) than the R-isomer [Jiang et al, 1999]. The same authors simultaneously evaluated the binding profile of pyridines obtained from the oxidation of the corresponding 1,4-dihydropyridines van Rhee et al, 1996]. These structures showed a general loss of selectivity at hA 3 , except for some derivatives substituted at the 4-position with small alkyl groups.…”
Section: A 3 Adenosine Receptor Antagonistsmentioning
confidence: 99%